Optimization of electronic speed governors sensitivity for marine diesel engines - Budurov, Mykola; Gorb, Sergii; Popovskii, Alexey (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is multicylinder marine diesel installations equipped with electronic speed governors (ESGs) operating under wave disturbance conditions. Modern marine diesel engines used in ship power plants are equipped with ESGs which have the technical capability to adjust the sensitivity of the governor’s input signal. This parameter allows modifying the governor’s response to high-frequency disturbances, which is a characteristic feature of diesel engine operation. However, assuming constant engine speed throughout the working cycle overly idealizes the governor’s input signal. This leads to distorted optimal settings and reduced speed stability, especially under variable load torque conditions on the propeller shaft. To improve the efficiency of the automatic speed control system, a specialized model of a multicylinder marine diesel engine as a speed control object has been developed. This model takes into account the influence of cyclic torque instability on the governor’s input signal across the entire operating range of diesel engines of various stroke types, speeds, and numbers of cylinders. For the two- and four-stroke marine main diesel engines HYUNDAI-MAN B&W 6S60MC-C7 and MaK 9M25C under study, modeling determined the governor sensitivity optimal settings for different sea wave disturbance intensities and periods. The model’s capabilities for calculating changes in cylinder gas pressure in diesel engines of different stroke types enable an analysis of non-uniformity in working processes during the optimization of ESGs and determining the optimal combination of their tuning parameters. These findings allow improving the stability of automatic speed regulation over the entire range of possible operating conditions of main marine diesel engines